The grey zone: the 'ordinary' violence of extraordinary times - Roy, Srila (Wiley-Blackwell, 2008)
The article analyses the 'ordinary' violence of revolutionary politics, particularly acts of gendered and sexual violence that tend to be neglected in the face of the 'extraordinariness' of political terror. Focusing on the extreme left Naxalbari movement of West Bengal, it points to those morally ambiguous 'grey zones' that confound the rigid distinctions between victim and victimizer in insurrectionary politics. Public and private recollections of sexual and gender-based injuries by women activists point to the complex intermeshing of different forms of violence (everyday, political, structural, symbolic) across 'safe' and 'unsafe' spaces, 'public' and 'private' worlds, and communities of trust and those of betrayal. In making sense of these memories and their largely secret or 'untellable' nature, the article places sexual violence on a continuum of multiple and interrelated forces that are both overt and symbolic, and include a society's ways of mourning some forms of violence and silencing others. The idea of a continuum explores the 'greyness' of violence as the very object of anthropological inquiry.